Nanofluid influenced convective heat transfer and nanoparticles dispersion in porous media with a two-phase lattice Boltzmann analysis - Aliu, O. (John Wiley and Sons Inc, 2022)
In this study, a two-phase lattice Boltzmann model (LBM) is developed and verified to study natural convective heat transfer in a porous medium that is fully saturated with ZnâH2O nanofluid (NF). Zinc, being an environmentally friendly material, is selected as the nanoparticle (NP) here. WeÂ aimÂ to analyze NP heat enhancement augmentation and dispersion during NF transport at different Rayleigh number (Ra) values, various porosity ((Formula presented.)), and varying nanoparticle volume fraction (NVF). The equations of flow (velocity), temperature (energy), and NVF fields in porous media are solved numerically. Physical parameters of Rayleigh number, NVF, and Darcy number (Da) are varied to examine their effects on flow patterns (streamlines), temperature distribution (Isotherms), and NP spread (dispersion). Nusselt number is calculated to elucidate its relationship with Ra, Da, and NVF. Results show that Nusselt number increases upon Ra and Da numbers increment thereby accounting for convective heat transfer augmentation. However, it is noted that at Ra = 105; (Formula presented.), the effects of varying NVF are almost the same, thereby suggesting an optimum for positive NP effect. An improved NP dispersion leading to good suspension stability for optimum Zn NP performance is observed with a higher temperature gradient at (Formula presented.), (Formula presented.) compared to (Formula presented.), where NP sedimentation is noticed. Likewise, an increase of NVF suggests an increase in Nusselt number until a certain optimum. This study provides deeper insight into NP dynamics and their heat transfer behavior in porous media using LBM. Â© 2021 Wiley Periodicals LLC.